Prediction of Future Streamflow for Kurau River Basin using Artificial Neural Network (ANN) - Salleh, Nurshyma Asyikin; Mohd Arish, Nur Aini; Hamidon, Nuramidah; Abdullah, Nor Maizzaty (Progress in Engineering Application and Technology, 2021)
The reservoir are used for many purposes, among them are to provide reliable water supply, hydropower and flood mitigation. Due to climate change, the reservoirs are impacted by the increase in global surface temperature. This situation will then lead to the need for an assessment of regional climate change impacts. The objectives of this study are to develop the hydrological model for the Kurau River Basin which is the main water resource for the Kerian Irrigation scheme and the Bukit Merah reservior, to assess climate change impact on river runoff using artificial neural network (ANN) and to predict the future streamflow using Artificial Neural Network (ANN) from Statistical Downscaling Model (SDSM) output. The data for this research included the data for the past and present data from 2010 until 2020 and the future data prediction from 2020 until 2050 as the output data.